1999
DOI: 10.1046/j.1442-2050.1999.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of the ileocolic sphincter transplanted to the neck using microsurgery technique: a manometric study in dogs *

Abstract: The usefulness of ileocolic sphincter (ICS) transplantation to the neck after a total laryngopharyngectomy was investigated in 12 mongrel dogs. The authors aimed to evaluate the influence of the transplantation on ICS pressure amplitude and ICS length, and on ICS resistance to intracecal pressure increase. Electromanometric measurements showed that ICS pressure amplitude and length presented no changes after the procedure. Also, there was no significant change in ICS resistance. However, long-term follow-up st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…A perfusão do esôfago com ácido clorídrico tem sido estudada em inúmeras pesquisas experimentais. Na presente, o animal escolhido foi o cão, por se tratar de animal de fácil obtenção em nosso biotério (23,25) . Além disso, o cão é animal dócil, sendo possível sua utilização em estudos motores neste laboratório (3,11,22,23,25) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A perfusão do esôfago com ácido clorídrico tem sido estudada em inúmeras pesquisas experimentais. Na presente, o animal escolhido foi o cão, por se tratar de animal de fácil obtenção em nosso biotério (23,25) . Além disso, o cão é animal dócil, sendo possível sua utilização em estudos motores neste laboratório (3,11,22,23,25) .…”
Section: Discussionunclassified
“…A eletromanometria foi realizada através da técnica de puxada intermitente da sonda, usada em inúmeros trabalhos experimentais (14,23) e clínicos (6,15) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…7 The ileocolic valve (Bauhin's valve) resembles a flap valve, functions like a true sphincter and prevents retrograde passage through the valve. 8 With the use of this valve, aspiration through the phonatory shunt is prevented, while vocalization is allowed. However, an earlier evaluation suggested that better phonatory characteristics could be obtained using an electronic larynx, which makes it comparatively simple to produce an alaryngeal voice without additional surgery.…”
Section: Introductionmentioning
confidence: 99%